2014
DOI: 10.1097/01.inf.0000435502.36996.72
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Pediatric Sepsis Study, From the Spanish Society of Pediatric Intensive Care

Abstract: Patients with sepsis and multiorgan failure, especially those with nosocomial infection or the presence of neutropenia or purpura, have a worse prognosis and should be monitored and treated early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…The sample analyzed included 63.5% male patients, a number quite similar to the 2011 study ( 7 ) and similar to other previous studies. ( 14 - 18 ) The age analysis of this study’s patients showed they were mostly younger than 12 months (54.8%) and younger than 36 months in 73% of cases, which is similar to most studies.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The sample analyzed included 63.5% male patients, a number quite similar to the 2011 study ( 7 ) and similar to other previous studies. ( 14 - 18 ) The age analysis of this study’s patients showed they were mostly younger than 12 months (54.8%) and younger than 36 months in 73% of cases, which is similar to most studies.…”
Section: Discussionsupporting
confidence: 73%
“…The presence of comorbidities among the study’s children was small (24.3%) compared to the literature, which reports percentages ranging from 40 to 91%. ( 7 , 11 , 14 - 17 , 19 ) This finding reflects the characteristics of the setting in which the study was conducted, which was a pediatric ICU with a general profile of admissions for community-acquired clinical diseases.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations